MORPHOFUNCTIONAL STATUS OF ELITE SERBIAN TAEKWON-DO ATHLETES - Željko Rajković; Zoran Obradović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Results of testing taekwondo head team Serbia and Monte Negro may produce important information for coaches and their sportsman performance. The main object of this study was importance of detail analyses of specifi c sport activity with all details which are important for construction of the specifi c taekwon-do sport